Inovasi E-Modul Matakuliah Berbicara Dialektik pada Mahasiswa Prodi Pendidikan Bahasa dan Sastra Indonesia - Agung Nugroho; Rambat Nur Sasongko; Muhammad Kristiawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the development and design of a valid, practical and effective online-based Dialectical Speaking module for students of the Indonesian Language and Literature education program STKIP-PGRI Lubuklinggau. The method used is Research and Development (R&D) with the Dick & Carey model limited to 8 stages. The test results of the Dialectical Speaking module show that as many as six people get very good scores with a score of 80-100 (30%), nine people get a score of 66-79 in the good category (45%) and only one student who gets enough grades with a score of 58 or only 5% and students who get fewer scores are four people with a score range of 46-55 or 20%. In conclusion, the Dialectical Speaking module is suitable for second-semester students of the Indonesian Language and Literature Education Study Program at STKIP-PGRI Lubuklinggau. Keywords: Dialectical Speaking, E-Module, Innovation